2016
DOI: 10.21649/akemu.v10i2.1196
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABO, Rh blood groups systems with lipids and other anthropometric co variables as predictors of cardiovascular risk in NWFP, Pakistan

Abstract: Aims and Objects: The present study was carried out to find the possibility of association of lipid profile with ABO/Rh blood groups and other anthropometric co- variables as cardiovascular risk. Material and Methods: A community-based investigation was carried out on lipid profiles and blood groups of selected population of rural and urban areas of Peshawar. NWFP on total of 1304 subjects out of which 548 were females and 756 were males. Age ranged from 16-75 years. Due emphasis was laid in the study on anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A study conducted by Shamim and Ihtesham in NWFP to find the possibility of association between blood groups and lipid profile revealed that B and O phenotypes have relatively greater disturbances in lipid profile than other blood groups [68].…”
Section: Association With Dyslipidemiamentioning
confidence: 99%
“…A study conducted by Shamim and Ihtesham in NWFP to find the possibility of association between blood groups and lipid profile revealed that B and O phenotypes have relatively greater disturbances in lipid profile than other blood groups [68].…”
Section: Association With Dyslipidemiamentioning
confidence: 99%